1987
DOI: 10.1139/b87-330
|View full text |Cite
|
Sign up to set email alerts
|

Fossil chrysophycean cyst flora in a small meromictic lake in southern Ontario, and its paleoecological interpretation

Abstract: Fossil chrysophycean cysts were identified and counted from the laminated sediment core from Crawford Lake. Thirty-two morphotypes have been described, most of them for the first time. The detailed description of the cysts is presented, including scanning electron photomicrographs. The abundance of certain morphotypes appears to be related to lake paleoproductivity. On this basis, fossil cyst flora have been divided into three characteristic groups: eutrophic–, mesotrophic–, and oligotrophic–meromictic forms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Wilkinson et al (1999) observed the same relationship with Na + and dissolved TP for Dinobryon cylindricum (cyst 41), which is corroborated by this study (Figure 3). D. cylindricum has formerly been described as typical of cool, oligotrophic to mildly eutrophic waters (Rybak 1986;Rybak et al 1987;Eloranta 1989;Siver 1995) and appears to be fairly representative of arctic environments (Duff and Smol 1989). There is, however, some debate about its pH optimum.…”
Section: Cyst Autecologymentioning
confidence: 99%
“…Wilkinson et al (1999) observed the same relationship with Na + and dissolved TP for Dinobryon cylindricum (cyst 41), which is corroborated by this study (Figure 3). D. cylindricum has formerly been described as typical of cool, oligotrophic to mildly eutrophic waters (Rybak 1986;Rybak et al 1987;Eloranta 1989;Siver 1995) and appears to be fairly representative of arctic environments (Duff and Smol 1989). There is, however, some debate about its pH optimum.…”
Section: Cyst Autecologymentioning
confidence: 99%
“…13). Similar cysts include: Nygaard (1956) -cysta microspinosa, cysta stellata; Rybak (1986Rybak ( , 1987, Rybak et al (1987) -cysta stellata (Kortowskie Lake), cyst 23 (Racze lake), cyst 19 (Crawford Lake); Smith & White (1985) - Fig. 14 (Coldwater Lake); Duff & Smol (1989, 1991 -type 33 (Tasikutaaq Lake), type91 (Upper Wallface Pond). , 1980b is not.…”
Section: Cyst # 3 (Fig 5; Negative No Eb37-007) (Diameter: 4-7 I~m)mentioning
confidence: 99%
“…The surface is quite smooth to micro-textured. This cyst type is distributed quite widely: Nygaard (1956), Carney & S andgren (1983) -cysta curvieollis; -cyst 9; , 1980b, Adam & Mehringer (1980a) -type 56 (Upper Echo Lake, Alta Morris Lake, Lost Trail Pass Bog, Lake Aloha); Rybak (1986) -cysta curvicollis (Kortowskie Lake); Rybak et al (1987) -cyst 3 (Crawford Lake); Duff& Smol (1989) cyst 41 (Tasikutaaq Lake). This cyst type is probably produced primarily by Dinobryon cylindricum Imhof.…”
Section: Cyst # 13 (Fig 14; Negative No L450-005) (Diameter: 35-7mentioning
confidence: 99%
“…These changes in accumulation rates were closely correlated with trends in lake productivity as indicated by changes in fossil pigments and diatoms (see below) as well as chrysophycean cysts (Rybak et al, 1987b) .…”
Section: Methodsmentioning
confidence: 63%